2016
DOI: 10.1177/0960327115614384
|View full text |Cite
|
Sign up to set email alerts
|

A model of chlorpyrifos distribution and its biochemical effects on the liver and kidneys of rats

Abstract: This study investigated the main target sites of chlorpyrifos (CPF), its effect on biochemical indices, and the pathological changes observed in rat liver and kidney function using gas chromatography/mass spectrometry. Adult female Wistar rats ( n = 12) were randomly assigned into two groups (one control and one test group; n = 6 each). The test group received CPF via oral gavage for 21 days at 5 mg/kg daily. The distribution of CPF was determined in various organs (liver, brain, heart, lung, kidney, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 57 publications
(102 reference statements)
2
34
0
1
Order By: Relevance
“…The release of these enzymes could further lead to hepatic necrosis and inflammatory reactions. The elevation in ALT activity level observed in the present study in rats chronically exposed to CPF agrees with the findings from previous studies in laboratory animals (Yoshida et al, 1985;Tanvir et al, 2015Tanvir et al, , 2016. Similarly, results obtained from a study involving pesticide sprayers have shown high liver enzyme activities in the serum of these subjects (Patil et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…The release of these enzymes could further lead to hepatic necrosis and inflammatory reactions. The elevation in ALT activity level observed in the present study in rats chronically exposed to CPF agrees with the findings from previous studies in laboratory animals (Yoshida et al, 1985;Tanvir et al, 2015Tanvir et al, , 2016. Similarly, results obtained from a study involving pesticide sprayers have shown high liver enzyme activities in the serum of these subjects (Patil et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…As insulin is an important regulatory factor of lipid metabolism [ 36 ], one can assume that an alteration in insulin secretion perhaps modified the triglyceride content. Other mechanisms can also contribute to the disturbance of triglyceride synthesis, notably the ones targeting adipose tissue and/or liver signaling that are essential for homeostasis regulation [ 37 , 38 ]. We recently reported that CPF exposure increased para-cellular permeability in the small intestine [ 39 ] and delayed intestinal epithelial maturation [ 25 ], which may suggest a modification of intestinal absorption of triglycerides in the blood stream.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively long half-life of TCPy might be related to the much higher lipophilicity of chlorpyrifos and CP-me (with log K ow of 4.96 and 4.13, Table S2) than TCPy (with log K ow of 1.22). As reported by animal experiments, chlorpyrifos can concentrate in the body tissues of rats, particularly in adipose tissues (Tanvir et al, 2015). Therefore, in addition to those eliminated as urinary TCPy, chlorpyrifos (or CP-me) exposed in farmers might also concentrate in human body tissues, which weakening the increase in the urinary levels of chlorpyrifos and CP-me.…”
Section: Elimination Rate Of Chlorpyrifos In Farmers After Pesticide mentioning
confidence: 91%